Trade in services : a case for open markets - Aronson, Jonathan David; Cowhey, Peter F. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1984)
The book governs various activities that do not neatly fit together except that they are not manufactured and commodity goods. Therefore, before we analyze the options for government policy, we summarize the basic facts about services in world trade and the U.S. economy.
Bibliography: p. 41-46.
gau 27/02/17
Loans
Keywords: Service industries; Service industries